2010
DOI: 10.1126/science.1181185
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio cholerae VpsT Regulates Matrix Production and Motility by Directly Sensing Cyclic di-GMP

Abstract: Microorganisms can switch from a planktonic, free-swimming life style to a sessile, colonial state, called a biofilm, conferring resistance to environmental stress. Conversion between the motile and biofilm life style has been attributed to increased levels of the prokaryotic second messenger cyclic di-guanosine monophosphate (c-di-GMP), yet the signaling mechanisms mediating such a global switch are poorly understood. Here we show that the transcriptional regulator VpsT from Vibrio cholerae directly senses c-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
500
2
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 383 publications
(524 citation statements)
references
References 17 publications
9
500
2
5
Order By: Relevance
“…Pel polysaccharide biosynthesis is furthermore regulated in P. aeruginosa by the c-di-GMP receptor protein PelD (91). Recently, a novel c-di-GMP protein that triggers attachment by inducing polysaccharide production was identified in V. cholerae (83). This work demonstrated that the transcriptional regulator VpsT directly senses c-di-GMP to inversely control Vps polysaccharide production and motility.…”
Section: Modulation Of Cyclic Di-gmpmentioning
confidence: 85%
See 1 more Smart Citation
“…Pel polysaccharide biosynthesis is furthermore regulated in P. aeruginosa by the c-di-GMP receptor protein PelD (91). Recently, a novel c-di-GMP protein that triggers attachment by inducing polysaccharide production was identified in V. cholerae (83). This work demonstrated that the transcriptional regulator VpsT directly senses c-di-GMP to inversely control Vps polysaccharide production and motility.…”
Section: Modulation Of Cyclic Di-gmpmentioning
confidence: 85%
“…This work demonstrated that the transcriptional regulator VpsT directly senses c-di-GMP to inversely control Vps polysaccharide production and motility. The effect on VpsT, the master regulator for biofilm formation, was found to be due to a change in oligomerization upon c-di-GMP binding rather than phosphorylation (83).…”
Section: Modulation Of Cyclic Di-gmpmentioning
confidence: 99%
“…The affinity of these RNAs for their ligand is very high; class I riboswitches have a K d as tight as 10 pM (23) (1,2,(9)(10)(11)(12)(13)(14)(15)(16). Whereas a few bacteria contain examples of both classes, several species lacking a class I riboswitch use c-di-GMP for signaling and have exclusively a class II riboswitch (19).…”
mentioning
confidence: 99%
“…To alter gene expression or protein activity in response to external or internal signals, c-di-GMP interacts with several proteins (1,2,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). In addition, two classes of RNAs have been reported that bind this second messenger, the c-di-GMP-I (class I) and c-di-GMP-II (class II) riboswitches (18,19).…”
mentioning
confidence: 99%
“…An increasing number of proteins responsive to c-di-GMP has been identified (reviewed by Hengge, 2009), including several DNA-binding proteins, i.e. the FleQ regulator in Pseudomonas aeruginosa (Hickman & Harwood, 2008), the VpsT protein in Vibrio cholerae (Krasteva et al, 2010) and the CLP protein in Xanthomonas campestris (Chin et al, 2010). In addition, c-di-GMP can regulate gene expression through direct binding to riboswitch elements in mRNAs (Sudarsan et al, 2008), bypassing the need for c-di-GMPbinding regulatory proteins.…”
Section: Introductionmentioning
confidence: 99%